Utilization of Coconut Water for Increasing the Growth of Shoot Cutting of Meranti Tembaga (Shorea leprosula Miq.) - Edje Djamhuri (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2011)
Coconut water contains gibberelin, cytokinin and auxin which have potential to stimulate the growth of cuttings. The objective of this research was learning the effect of application of coconut water, IBA and NAA on the growth of shoot cuttings of meranti tembaga (Shorea leprosula). This research was conducted in nursery of Division of Silviculture, Department of Silviculture, Faculty of Forestry, Bogor Agriculture University, for 4 month. The research used Completely Randomized Design, comprising 4 treatment, namely control, application of coconut water, IBA of 100 ppm, and NAA of 100 ppm, with three replication, and each replication consisted of 20 shoot cuttings. Growth parameters of shoot cuttings comprised percentage of survival, percentage of shoot growth, percentage of rooting, and dry weight of roots. Research result showed that application of coconut water, equivalent with IBA of 100 ppm and NAA of 100 ppm could increase the growth of meranti tembaga (Shorea leprosula) shoot cutting. Coconut water could be used to stimulate the growth of meranti tembaga shoot cutting as a substitute for IBA of 100 ppm or NAA of 100 ppm.